2019
DOI: 10.1073/pnas.1817431116
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, prominence, and the effects of academic environment

Abstract: Faculty at prestigious institutions produce more scientific papers, receive more citations and scholarly awards, and are typically trained at more-prestigious institutions than faculty with less prestigious appointments. This imbalance is often attributed to a meritocratic system that sorts individuals into more-prestigious positions according to their reputation, past achievements, and potential for future scholarly impact. Here, we investigate the determinants of scholarly productivity and measure their depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
121
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(142 citation statements)
references
References 33 publications
5
121
0
1
Order By: Relevance
“…Since participants who graduate from better universities will have better education and research resources and may carry this on to their working environments [47]; however, we found no correlation between graduate school and HRC. A study found that the training and work environments but not the prestige of their doctoral institution drove researcher productivity [48], similar to that observed herein. Degree and graduate school were often used as a measure of scientific capacity [49]; therefore, our results may provide a perspective for hospital administrators for what may be considered when bringing in talents and improving hospital research capacity.…”
Section: Discussionsupporting
confidence: 80%
“…Since participants who graduate from better universities will have better education and research resources and may carry this on to their working environments [47]; however, we found no correlation between graduate school and HRC. A study found that the training and work environments but not the prestige of their doctoral institution drove researcher productivity [48], similar to that observed herein. Degree and graduate school were often used as a measure of scientific capacity [49]; therefore, our results may provide a perspective for hospital administrators for what may be considered when bringing in talents and improving hospital research capacity.…”
Section: Discussionsupporting
confidence: 80%
“…The assessment of researchers has been under scrutiny for some time ( McKiernan et al, 2019 ; Moher et al, 2018 ; Way et al, 2019 ; Weingart, 2005 ). They are immersed in a reward system that evaluates them individually following uniform expectations of leadership and excellence ( Bol et al, 2018 ; Merton, 1968 ; Reskin, 1977 ).…”
Section: Discussionmentioning
confidence: 99%
“…Private institutions in the United States are often associated with greater prestige than their public counterparts, evidenced by the consistently higher rankings of American private institutions in national and global ranking schema (e.g., US News & World Report; Times Higher Education). Clauset et al (2015) found that increased institutional prestige is related to increased faculty production, and Way et al (2019) report that the prestige of a researcher's place of work, rather than the prestige of the doctoral program where they trained, has a positive effect on their scholarly productivity. Our data do not allow direct testing of doctoral program versus current workplace prestige, but our findings add "OA article authorships" to the growing list of scholarly productivity indicators that appear to increase with the prestige of a researcher's current institution.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively new field of the science of science has provided valuable insights into the role of institutional prestige in knowledge production (Clauset et al, 2015;Way et al, 2019). As Way et al note, research on the science of science sometimes falsely "…assumes, implicitly if not explicitly, that meritocratic principles or mechanisms govern the production of knowledge."…”
Section: Discussionmentioning
confidence: 99%